nuKSM: NUMA-aware Memory De-duplication on Multi-socket Servers - Panda, Akash; Panwar, Ashish; Basu, Arkaprava (2021 International Conference on Parallel Architectures and Compilation Techniques, 2021)
An operating system has many memory management goals including reducing memory access latency, and reducing memory footprint. These goals can conflict with each other when independent subsystems optimize them in silos. In this work, we report one such conflict that appears between memory de-duplication and NUMA (non-uniform memory access) management. Linux's memory de-duplication subsystem, namely KSM, is NUMA unaware. Consequently, while de-duplicating pages across NUMA nodes, it can place de-duplicated pages in a manner that can lead to significant performance variations, unfairness, and subvert process priority. Toward this, we introduce NUMA-aware KSM, a.k.a., nuKSM, that makes judicious decisions about the placement of de-duplicated pages to reduce the impact of NUMA, unfairness, and avoid priority subversion. Independent of the NUMA effects, we observed that KSM scales poorly to systems with larger memory sizes due to its centralized design. Thus, we extended nuKSM to adopt a de-centralized design.